Genome-wide association study shows BCL11A associated with persistent fetal hemoglobin and amelioration of the phenotype of beta-thalassemia - Uda, Manuela; Galanello, Renzo; Sanna, Serena; Lettre, Guillaume; Sankaran, Vijay G; Chen, Weimin; Usala, Gianluca; Busonero, Fabio; Maschio, Andrea; Albai, Giuseppe; Piras, Maria Grazia; Sestu, Natascia; et al. (Proceedings of the National Academy of Sciences - PNAS, 2008)
beta-Thalassemia and sickle cell disease both display a great deal of phenotypic heterogeneity, despite being generally thought of as simple Mendelian diseases. The reasons for this are not well understood, although the level of fetal hemoglobin (HbF) is one well characterized ameliorating factor in both of these conditions. To better understand the genetic basis of this heterogeneity, we carried out genome-wide scans with 362,129 common SNPs on 4,305 Sardinians to look for genetic linkage and association with HbF levels, as well as other red blood cell-related traits. Among major variants affecting HbF levels, SNP rs11886868 in the BCL11A gene was strongly associated with this trait (P < 10(-35)). The C allele frequency was significantly higher in Sardinian individuals with elevated HbF levels, detected by screening for beta-thalassemia, and patients with attenuated forms of beta-thalassemia vs. those with thalassemia major. We also show that the same BCL11A variant is strongly associated with HbF levels in a large cohort of sickle cell patients. These results indicate that BCL11A variants, by modulating HbF levels, act as an important ameliorating factor of the beta-thalassemia phenotype, and it is likely they could help ameliorate other hemoglobin disorders. We expect our findings will help to characterize the molecular mechanisms of fetal globin regulation and could eventually contribute to the development of new therapeutic approaches for beta-thalassemia and sickle cell anemia.